ORGANISASI TRADISIONAL DITINJAU DARI SISTEM DEMOKRASI DI INDODESIA - Ni Ketut Tri Srilaksmi; I Wayan Suarjaya (Sekolah Tinggi Agama Hindu Mpu Kuturan Singaraja, 2018)
The Hulu Apad is a sporadic traditional Balinese organisation that is developing mainly in highland areas of the island. This writing studies the traditional Pakraman system of the organisation when seen from the Indonesian governmental democratic point of view, namely the process of deciding the system, the main task, and the function of every representation of the organisation at a village.